An MPC-based position controller for a tilt-rotor tricopter VTOL UAV - Prach, Anna (2018)
This study presents a novel framework, namely, the fusion of a conventional controller and a linear model predictive controller, for the position control of a tilt-rotor tricopter. While the conventional controller in the outer loop is responsible for the position control, the inner-loop model predictive control–based controller handles the angular dynamics and vertical body velocity. Furthermore, a novel control allocation algorithm for the proposed controller is introduced. In addition, this study also covers mathematical modeling and trim analysis of the tilt-rotor tricopter dynamics. An evaluation of the designed control system is accomplished with a nonlinear 6-degree-of-freedom simulation model of the tilt-rotor tricopter in which realistic actuator limitations are considered. The efficiency of the proposed control algorithm is elaborated for a trajectory tracking problem where basic surveillance operation is considered. The simulation results show that the proposed model predictive controller is able to provide a satisfactory trajectory tracking performance under the realistic actuator limits.